Antioxidant and UV Protection Activities of Squid (Loligo sp.) Ink Powder Lotions - Dyah Rahmasari; Aulia Juwanti; Ima Pratiwi; Novia Zulfa Diana; Raditya Weka Nugraheni; Dita Nurlita Rakhma (Borneo Journal of Pharmacy, 2021)
Melanin is a pigment contains in human skin which role as a UV-absorbing agent. One of the exogenous melanins can be obtained from squid (Loligo sp.) ink. Squid ink melanin has potent free radical protection activities. This study aimed to determine the physicochemical, stability, antioxidant, and UV protection activities of squid ink powder lotions. Squid ink powders were obtained from the drying process using HCl 0.5M and stored in the climatic chamber. Antioxidant activity was conducted quantitatively using the DPPH (2,2-diphenyl-1-picrylhydrazil) scavenging method. The best result of the DPPH scavenging activity was 29.12±0.023%, shown from formula III. UV protection activity was conducted by observing erythema scores in animal skin, which exposure to UV. This preparation inhibits the effect of UV exposure. Squid ink powder lotions are potential as a sunscreen product.